PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAME EDUKASI WORDWALL TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SDN 142 PALEMBANG - Masnunah; Try Kurnianingsih; Sylvia Lara Syaflin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Effect of Using the Educational Game Media Wordwall on Student Learning Outcomes in Indonesian Language Subjects for Grade V Students at SDN 142 Palembang.The educational game Wordwall is an interactive online game that can be accessed via browser and utilized as a learning resource for students. Wordwall serves as an engaging learning medium that can help improve student learning outcomes, especially in the subject of Indonesian language. In Indonesian language learning at the elementary school level, there are four core language skills: listening, speaking, reading, and writing. Every lesson delivered to students results in measurable learning outcomes. Therefore, this study aims to determine the effect of using Wordwall educational game media on the learning outcomes of Grade V students in Indonesian language subjects at SDN 142 Palembang. This research employed a quantitative method with a percentage approach. After collecting the required data, it was classified according to the predetermined formulation. The results of the study show that the use of Wordwall educational game media in Indonesian language learning positively affects student learning outcomes, particularly in fostering environmental awareness among Grade V students at SDN 142 Palembang. This is evidenced by the statistical result where the t value of 7.901 is greater than the t table value of 2.024. This indicates that the use of Wordwall educational game media significantly influences the Indonesian language learning outcomes of Grade V students.